Evaluasi Penggunaan Obat pada Pasien Rawat Inap Skizofrenia Paranoid di RSI Banjarnegara Tahun 2024 - Kholid, Rofik; Dewi, Iva Rinia; Dewi, Hika Dwi Kartina (Sultan Agung Islamic University of Semarang, 2025)
Background: Paranoid schizophrenia, the most common form of schizophrenia characterized by delusions and hallucinations, is typically treated with antipsychotic medications. This research aimed to evaluate the medication use in 75 patients with paranoid schizophrenia at RSI Banjarnegara by adhering to the